2009
DOI: 10.1021/ac901663x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Hydrothermal Growth of Metal−Organic Framework 199 Films on Stainless Steel Fibers for Solid-Phase Microextraction of Gaseous Benzene Homologues

Abstract: Metal-organic frameworks (MOFs) have received great attention due to their fascinating structures and intriguing potential applications in various fields. Herein, we report the first example of the utilization of MOFs for solid-phase microextraction (SPME). MOF-199 with unique pores and open metal sites (Lewis acid sites) was employed as the coating for SPME fiber to extract volatile and harmful benzene homologues. The SPME fiber was fabricated by in situ hydrothermal growth of thin MOF-199 films on etched sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
170
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 359 publications
(172 citation statements)
references
References 52 publications
2
170
0
Order By: Relevance
“…MOF-199 was the first reported MOF utilized as an SPME fiber coating material. It was immobilized on etched stainless wire via an in situ hydrothermal method [148]. This homemade fiber exhibited wide linear ranges, low detection limits, high enrichment factors, and higher extraction efficiencies than the commercial SPME/DVB fiber with benzene homologues as the target analytes.…”
Section: Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…MOF-199 was the first reported MOF utilized as an SPME fiber coating material. It was immobilized on etched stainless wire via an in situ hydrothermal method [148]. This homemade fiber exhibited wide linear ranges, low detection limits, high enrichment factors, and higher extraction efficiencies than the commercial SPME/DVB fiber with benzene homologues as the target analytes.…”
Section: Mofsmentioning
confidence: 99%
“…Cui et al [148] observed that humidity decreased the extraction efficiencies, since the coordination structure would be unstable under certain humidity. Some MOFs are stable to humidity and water, such as MIL-53 [156] and [Cd(L) 2 (ClO 4 ) 2 ]ÁH 2 O (L = 4-amino-3,5-bis(4-pyridyl-3-phenyl)- [157], which were used for DI SPME in aqueous solutions.…”
Section: Mofsmentioning
confidence: 99%
“…As an efficient and remarkable sample preparation technique, solidphase microextraction (SPME) has attracted increasing attention due to its high efficiency, simplicity, solvent-free and facilitation in automation and coupling techniques [2][3][4]. In general, the fiber coating is considered to be the key factor in SPME technique [5][6][7]. Till now, the varieties of commercially available SPME fibers are increasing.…”
Section: Introductionmentioning
confidence: 99%
“…For new coating materials, high-porosity materials have attracted much attention recently because of their large specific surface areas and high extraction capacities resulting in significant improvement in sensitivity, such as carbon nanotubes [15], graphene [16,17] and metal-organic framework [7]. Mesoporous materials are considered the high-efficiency sorbents due to high specific surface area, controllable pore size, narrow pore size distribution, thermal and mechanical stability, which have various applications in chemical industry [18,19], environment [10,[18][19][20], medicine [21,22], adsorption and separation [23].…”
Section: Introductionmentioning
confidence: 99%
“…Although these commercial fibers have been successfully applied in many fields, some of them still have drawbacks, such as high cost, nonresistance to high temperature and organic solvents, low extraction efficiency (especially for polar and ionic compounds), and selectivity, etc. To overcome these disadvantages, new SPME coatings with remarkable properties have been developed continually using new preparation methods, including direct use of uncoated fibers [8], sol-gel technology [9], epoxy-glued solid sorbents [10], electrochemical modification [11] and physical deposition [12], or new materials [13,14].…”
Section: Introductionmentioning
confidence: 99%